AB0508 Clinically amiopathic dermatomyositis: comparison with classical dermatomyositis and description of clinical outcome. (23rd January 2014) - Barsotti, S.; Neri, R.; Iacopetti, V.; Mosca, M.; Tripoli, A.; d'Ascanio, A.; Tavoni, A. G.; Della Rossa, A.; Bombardieri, S.
Abstract : Background: Clinically amiopathic dermatomyositis (CADM) is characterized by the presence of dermatological features similar to DM without clinical signs of muscular involvement. CADM is further distinguishable in amiopathical DM (ADM) and hypomyopathical DM (HDM) if muscular involvement is absent or detectable only with instrumental investigation. Objectives: to compare classical DM with CADM and to describe clinical features, treatment and outcome of CADM. Methods: Patients with DM and CADM followed at our institute were evaluated. Demographic, clinical (muscular and extramuscular involvement), laboratory (creatine-kinase, ANA/ENA) and instrumental/histological features (EMG, esophagus rx, chest rx, capillaroscopy, muscle biopsy) of patients at the time of diagnosis were collected from clinical charts. Results: 103 patients (32 male, 71 female) were included: 95 DM and 8 CADM. The mean age at myositis onset was respectively 43 and 54 years; the mean follow-up duration is respectively 40 and 77 months. Muscular weakness and myalgia were observed in 64/92 (70%) and 31/90 DM cases (34%) respectively. In CADM no clinical signs of muscular involvement were observed. Heliotrope rash was present in 61/93 DM (66%) and in 7/8 (87.5%) CADM patients. Gottron's papules/sign were present in 43/93 DM (46%) and 4/8 CADM (50%). Dyspnea, dysphagia, dysphonia, Raynaud were present in low percentages (5-19%) in both groups. CADM patients had normal creatine kinase levels (CK=51.2 UI/L), while in DM patients CK mean values were 2671 UI/L (p<0.0001). ANA were detectable in 54/93 (58%) DM and 2/8 (25%) CADM patients. ENA were not detectable in CADM group while in DM patients were positive in 12/89 (13.5%): 2 SSA, 3 Jo1, 1 RNP, 1 SSA/SSB, 5 unidentified specificity. Esopahageal xray showed hypotony/hypokinesis in 2/3 CADM patients (67%) and in 22/54 (41%) DM patients. A specific SSc/PDM pattern was found by capillaroscopy in 6/8 (75%) of CADM and in 32/54 (56%) of DM patients. Pulmonary fibrosis was observed in one CADM patient (12.5%) versus 28/81 (35%) DM patients. The association with malignancy was found in 22 DM (23%) and in one CADM patient (12.5%). Electromyography identified myopatic features in 71/80 (89%) DM and in 5/8 (62.5%) CADM patients (p=0.039); muscle histology showed myopatic aspects in 56/60 (93%) DM and in 3/4 (75%) CADM patients. CADM patients were treated with low/medium doses steroids, hydroxichloroquine and one DMARD (AZA, MTX, CYC, CYA) alone or in combination. At last observation all patients had a good outcome of cutaneous manifestations. No clinical signs of muscular involvement were observed. Conclusions: In our case serie the prevalence of CADM is 8.3% of the total DM, slightly lower than literature showing prevalence ranging between 10-20%. With respect to DM, patients with CADM have less frequently pulmonary fibrosis, while esophageal involvement as well as capillaroscopic abnormalities appear more common. Interestingly, in spite of the absence of overt muscular involvement and normal CK values, instrumental examinations show that the majority (6/8) of CADM patients have subclinical muscular involvement and can be classifiable as HDM. Whether and how the muscular involvement should be treated is still a matter of research. Disclosure of Interest: None Declared